PERANCANGAN SISTEM INFORMASI PENGELOLAAN SURAT MASUK DAN SURAT KELUAR PADA PT PROVICES INDONESIA - Mellani Ardiyanti Neorau; Adjat Sudradjat (Institut Bisnis Muhammadiyah Bekasi, 2022)
In today's digital era, the development of technology and information continues to grow more rapidly. With the existence of technology and information can help and facilitate humans in completing a job. However, currently there are those who use a manual system. One of them at PT. Provices Indonesia still uses a simple method in the process of managing incoming and outgoing mail, starting from recording incoming and outgoing letters in a book and inputting them using Microsoft Excel and the process of making reports is still simple. So that in the ongoing process it is possible for errors to occur in recording, data recap and delays insearching for the required data. The purpose of this study is to analyze the ongoing mail management system at PT Provices Indonesia and design an information system to maximize the management process. So it is hoped that the new system can reduce the occurrence of errors in managing letters and data processing becomes faster so that making reports does not take a long time and the reports generated are in accordance with existing data. In addition, the existence of a system can further support employee activities in managing letter data so that it becomes better.